Efek Kombinasi Relaksasi Autogenik dan Aromaterapi Lavender Terhadap Kadar Glukosa Darah Pada Pasien DM Tipe 2 - Diah Ratnawati; Tyas Aulia Hanani (Jurnal Kebidanan dan Kesehatan Tradisional, 2020)
Background: Elderly as a group at risk of susceptible to health problems due to physiological decline in the body, one of them is diabetes mellitus type 2. Elderly diabetes mellitus type 2 requires good management both pharmacologically and non pharmacologically. Non-pharmacological management that can control blood glucose levels in the elderly is autogenic relaxation therapy with lavender aromatherapy. Autogenic relaxation is mind body therapy that focuses on heart rate and breath regulation. Aromatherapy lavender is a therapy that uses essential oils that can calm the mind. This scientific work aims to analyze effect of combination therapy of autogenic relaxation and lavender aromatherapy to amount blood sugar in elderly people with diabetes mellitus type 2. Methods: This study used a quasi experimental pre test and post test method without control group. Sampling using a purposive sampling method of 16 respondents. Therapy is done 2 times a day for 15 minutes in each session within 30 days with 10 meetings and blood glucose checks. The analysis test used the paired T-Test. Results: The results of the Paired T-Test statistical test showed a significant decrease in average blood glucose levels of 83.75 mg/dL with a value of p = 0.000. Conclusion: Combination therapy of autogenic relaxation and lavenderaromatherapy are effective for reducing blood glucose levels. Therefore, it is expected that the elderly with diabetes mellitus type 2 can perform autogenic relaxation therapy and lavender aromatherapy routinely so that blood glucose levels can decrease.